Children’s Knowledge of the Letter as the Beginning of Literacy in Yogyakarta - Christianti, Martha (Universitas Negeri Semarang, 2017)
The development of literacy is evolving naturally like motor development, cognitive, and language. One characteristic of early childhood literacy is aware of the child recognize letters. This study aims to determine the knowledge of letters in children associated with the name of the letter. Results of the research survey conducted on children at random in five districts in Yogyakarta (n = 630) showed that 72% of children aged 4-6 years have knowledge of letter names. The results showed that; 85% of the study subjects children recognize letters O. Knowledge of the letter O is the most widely known to the child at the age of 4-6 years. This was followed by the letters A, C, and so on until the lowest is letter Q. Some of the things that affect children's knowledge of letter name associated typeface known in lowercase or uppercase letters, form letters are almost the same as visually, the difference mention of the letter, and the mention of the letters in sequence.